School inspection under attack. Franco’s repression of primary school inspectors in Navarra - Mikelarena Peña, Fernando (Historia y Memoria de la Educación, 2016)
This article analyses the sanctions and punishments suffered by five of the seven inspectors of primary education in Navarre in 1936. Navarre was among the provinces in which school inspectors were persecuted most intensely. The paper also examines records of purges, accusations and political responsibilities in addition to carrying out a comparison with repression targeting other levels of public education.